2006
DOI: 10.1029/2005jd006575
|View full text |Cite
|
Sign up to set email alerts
|

Dust model intercomparison (DMIP) study over Asia: Overview

Abstract: [1] An intercomparison study involving eight dust emission/transport models over Asia (DMIP) has been completed. Participating dust models utilize a variety of dust emission schemes, horizontal and vertical resolutions, numerical methods, and different meteorological models. Two huge dust episodes occurred in spring 2002 and were used for the DMIP study. Meteorological parameters, dust emission flux and dust concentration (diameter < 20 mm) are compared within the same domain on the basis of PM and NIES lidar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
201
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(210 citation statements)
references
References 35 publications
7
201
0
2
Order By: Relevance
“…Quantitative description of processes such as sandblasting and saltation bombardment in a chemistry transport model (CTM) requires knowledge of many parameters that can not be accurately characterized spatially and temporally, including surface wind speed, soil moisture, soil texture, surface cover type, and topography [Ginoux et al, 2001;Tegen et al, 2002;Zender et al, 2003]. Not surprisingly, recent estimates in CTMs span from a few hundreds to over 4000 Tg for annual global dust emissions [Huneeus et al, 2011] and vary by several orders of magnitude for emissions of dust events at regional scales [Uno et al, 2006]. An observation-based approach, therefore, is needed to reduce these large uncertainties in estimates of dust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative description of processes such as sandblasting and saltation bombardment in a chemistry transport model (CTM) requires knowledge of many parameters that can not be accurately characterized spatially and temporally, including surface wind speed, soil moisture, soil texture, surface cover type, and topography [Ginoux et al, 2001;Tegen et al, 2002;Zender et al, 2003]. Not surprisingly, recent estimates in CTMs span from a few hundreds to over 4000 Tg for annual global dust emissions [Huneeus et al, 2011] and vary by several orders of magnitude for emissions of dust events at regional scales [Uno et al, 2006]. An observation-based approach, therefore, is needed to reduce these large uncertainties in estimates of dust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complicated dependence of the dust emission process on land-surface conditions makes accurate estimation of the distribution and intensity of dust emissions difficult. In fact, a dust model intercomparison project (Uno et al 2006) found that dust emission amounts estimated by eight CTMs showed large variation, sometimes differing by a factor of ten. This result indicates that there is considerable uncertainty in the estimation of dust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The dust-emission process itself is another highly uncertain aspect of the overall dust process (Mikami et al 2005). It is difficult to measure it directly, and its estimation in models varies widely for different events (Uno et al 2006). Therefore, a data-assimilation technique is often used by researchers (Yumimoto 2008;Sekiyama et al 2010).…”
Section: Introductionmentioning
confidence: 99%